Relative importance of site, weather and Phytophthora cinnamomi in the decline and death of Eucalyptus marginata – jarrah dieback investigations in the 1970s to 1990s - Davison, Elaine (Springer Netherlands, 2018)
Jarrah dieback was the name given to the sudden death of Eucalyptus marginata in the southwest ofWestern Australia, a serious economic problem. Although deaths were attributed to Phytophthora cinnamomi in the 1960s, the supporting evidence was weak; these deficiencies were not realised until 1980. Renewed interest in jarrah pathology showed that the incidence and severity of root lesions caused by P. cinnamomi in live trees was low, but in recent deaths it could be isolated from the root collar and large roots of some, but not all trees. Jarrah deaths result from hydraulic failure, implying extensive sapwood damage. This is unlikely to result from P. cinnamomi infection, which preferentially invades phloem, but could result from waterlogging, which causes tyloses to form in xylem vessels so they no longer conduct water. Tylosed root sapwood has been reported from investigations into jarrah deaths. An interpretation of past deaths based on stress factors better fits where and when deaths occur. This is within 3 years of exceptionally heavy rainfall, an inciting factor. Predisposing conditions are sites with some form of poor drainage, such as water-gaining sites, or those with impeded sub-soil drainage. Recent logging further increases site wetness. Phytophthora cinnamomi should be seen as a contributing factor, which is normally compartmentalised by the host, but can spread extensively in dying trees.